Unveiling the processing mechanism of Hezi-decoction-processed Tiebangchui: a synthesis approach using UPLC-Q-TOF-MS-based metabolomics and DESI-MSI - Zhou, Zhen; Gao, Hui-Min; Pei, Zhao-Qin; Sha, Meng-Xiang; Li, Cong-Ying; Zhang, Yi; Su, Jin-Song; Liu, Yue; Meng, Xian-Li (Frontiers in Pharmacology, 2025)
IntroductionTiebangchui (TBC, Tibetan name: བང་ང་ནག་པ།), the dried tuberous root of Aconitum pendulum Busch. and Aconitum flavaum Hand.-Mazz., is a prevalent used Tibetan medicine, recognized for its significant therapeutic effects despite its high toxicity. It is commonly employed in treating the diseases categorized as “Long” (རླུང་ནད།), cold, “Huang-shui” (སེར་ཆུ་ནད།), leprosy, and mania in Tibetan medicine. Notably, it is utilized in the treatment of rheumatoid arthritis, which is classified under the “Huang-shui” disease category according to Tibetan medical theory. Given its considerable toxicity, various processing techniques aimed at reducing the harmful effects of TBC are essential for its safe application in clinical settings. Hezi-decoction-processed method is a distinctive and effective traditional processing method of Tibetan medicine, but the overall variability of chemical constituents in the Hezi-decoction-processed TBC is still unclear. This investigation sought to examine a variety of diterpenoid alkaloids and tanning constituents, identify potential metabolic markers for differentiating the unprocessed TBC and Hezi-decoction-processed TBC at varying processing times, and determine the optimal processing time for reducing toxicity and maintaining efficacy.MethodsA combination of metabolomic techniques was developed, integrating ultra-high-performance liquid chromatography-quadrupole time-of-flight mass spectrometry (UPLC-Q-TOF-MS) with desorption electrospray ionisation mass spectrometry imaging (DESI-MSI) coupled with quantitative analytical techniques. This was done with the objective of monitoring the dynamic alterations in chemical constituents in TBC during the processing time. Metabolic markers were observed via DESI-MSI, and three alkaloids and five tannin acids were quantified through the use of UPLC and HPLC.ResultsFifty-one compounds were identified in unprocessed TBC and processed samples, of which 31 were discernible from unprocessed TBC. A total of 22 metabolic markers, such as aconine, aconitine, benzoylaconine, chebulic acid, gallic acid, and corilagin, can proficiently distinguish between raw and processed TBC with different processing times. And the results of content determination of three alkaloids and five tannins showed that they were stabilized at 72 h. The monoester-diterpenoid alkaloids (MDAs) and diester-diterpenoid alkaloids (DDAs) levels were 0.0149% and 0.0852% in 72 h, respectively. The contents of gallic acid, corilagin, 1,2,3,4,6-O-pentagalloylglucose, chebulinic acid, and ellagic acid were 8.9706, 9.3444, 1.2438, 5.7582, and 3.1160 mg/g, respectively. The distribution and accumulation of metabolic markers during processing were investigated by DESI-MS. The results of DESI-MSI were consistent with those of content determination experiments. Combined with the multivariate statistical analysis, content determination of three alkaloids and five tannin acids and DESI-MSI, 72 h is demonstrated to be the appropriate time for toxicity attenuation and efficacy reservation of TBC.DiscussionThe implementation of this technique could contribute to the identification of markers in Hezi decoction-processed TBC and the establishment of effective quality control and evaluation procedures to ensure the safety of TBC. The proposed method has the potential to elucidate the processing mechanism of Aconitum medicines and other toxic traditional Chinese medicines, given its wide applicability.